Perihelion Precessions of Inner Planets in Einstein’s Theory and Predicted Values for the Cosmological Constant - Alvaro H. Salas S; Jairo E Castillo H; Lorenzo J. Martınez H (The Scientific World Journal)
In this paper, we obtain the approximate value of 42.9815 arcsec/century for Mercury’s perihelion precession by solving both numerically and analytically the nonlinear ordinary differential equation derived from the geodesic equation in Einstein’s Theory of Relativity. We also compare our result with known results, and we illustrate graphically the way Mercury’s perihelion moves. The results we obtained are applicable to any body that moves around the Sun. We give predictions about the value of the Cosmological Constant. Simple algebraic formulas allow to estimate perihelion shifts with high accuracy.